Substantiation of economic efficiency of using a solar dryer under conditions of personal peasant farms - Babych, Mykhailo; Korobka, Svetlana; Skrynkovskyy, Ruslan; Korobka, Serhiy; Krygul, Roman (Eastern-European Journal of Enterprise Technologies, 2016)
A new design of a solar dryer for drying fruits is proposed, which includes the use of a flat mirror concentrator to enhance the flow of slant morning and evening sunlight, and a thermal accumulator based on pebble for accumulating over night time the excess heat from the reserve source of energy. This makes it possible to increase economic efficiency of the drying process by 20 %, to reduce energy consumption by 15 %, specific energy consumption by 10 %, direct operating costs by 5 %, electricity consumption by 3,4 kW·h, or 12384 kJ of thermal energy, by using solar energy. We improved a technique of the substantiation of economic efficiency of the developed solar dryer, the basis of which is a simplified mechanism for calculating direct operating costs, economic effect and payback period of the machine depending on the fluctuation of prices for electricity and dried products, linked to a specific territory of the location of a personal peasant farm. The results that were obtained can be used when developing and improving technical means of drying fruits, to improve technological, energy, biological and economic efficiency of the process.